Low-temperature electron–electron interaction correction to the anomalous Hall effect in Fe3GaTe2 single crystals - Dong, Yihui; Long, Xiuming; Lv, Xiaowei; Huang, Yalei; Zhang, Mingqian; Che, Renchao; Cao, Guixin (Journal of physics. Condensed matter, 2025)
The electron-electron interaction (EEI), weak localization and Kondo effect are known to correct low-temperature (low-T) resistivity in metals and semimetals. However, the impact of EEI on the anomalous Hall effect (AHE) by EEI remains a subject of debate. In this study, we investigate the EEI corrections to both the low-T longitudinal and anomalous Hall resistivities in van der Waals ferromagnetic Fe3GaTe2 single crystals with a high Curie temperature. Our findings reveal that the longitudinal resistivity is well-described by the EEI theory developed by Altshuler et al., while the anomalous Hall (AH) resistivity deviates from this theory. We found that the AH resistivity follows a T temperature dependence, and its relative rate of change is 2.6 times that of the longitudinal resistivity. These results demonstrate that EEI significantly influences the low-T AH resistivity under intrinsic mechanism in Fe3GaTe2. This observation challenges the conventional understanding that EEI does not contribute to the AHE in systems with mirror symmetry, as suggested by skew scattering and side jump models. This work opens avenues for further exploration of EEI effect in disordered magnetic materials.&#xD.The electron-electron interaction (EEI), weak localization and Kondo effect are known to correct low-temperature (low-T) resistivity in metals and semimetals. However, the impact of EEI on the anomalous Hall effect (AHE) by EEI remains a subject of debate. In this study, we investigate the EEI corrections to both the low-T longitudinal and anomalous Hall resistivities in van der Waals ferromagnetic Fe3GaTe2 single crystals with a high Curie temperature. Our findings reveal that the longitudinal resistivity is well-described by the EEI theory developed by Altshuler et al., while the anomalous Hall (AH) resistivity deviates from this theory. We found that the AH resistivity follows a T temperature dependence, and its relative rate of change is 2.6 times that of the longitudinal resistivity. These results demonstrate that EEI significantly influences the low-T AH resistivity under intrinsic mechanism in Fe3GaTe2. This observation challenges the conventional understanding that EEI does not contribute to the AHE in systems with mirror symmetry, as suggested by skew scattering and side jump models. This work opens avenues for further exploration of EEI effect in disordered magnetic materials.&#xD.